2018
DOI: 10.1002/eji.201747227
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils are not essential for maintenance of murine plasma cells in the bone marrow

Abstract: Eosinophils were reported to serve as an essential component of the plasma cell niche within the bone marrow. As the potential contribution of eosinophils to humoral immunity has remained incompletely understood, we aimed to further characterize their role during antibody responses and to additionally investigate their role in autoimmune disease. Contrary to our expectations and the currently prevailing paradigm, we found that eosinophils are fully dispensable for the survival of murine bone marrow plasma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
1
24
1
Order By: Relevance
“…Although it may not be expected that differences in the mucosal microbiota would influence plasma cell frequencies in the BM, it has long been appreciated that a large fraction of BM PCs in people secrete IgA, and in unpublished data we have noted that overall frequencies of total immature and mature BM plasma cells can vary greatly depending on the animal colony in which the mice in question are housed. Therefore, one potential explanation for the observed discrepancies between Chu et al versus the data reported here and by Haberland et al [20], is that the modest impact of eosinophil loss on BM PC pools can be realized only in the context of additional signals generated by unique collections of microbes. In this regard, it will be important to distinguish the impact of the microbiota on immature versus mature PC pools in the BM and elsewhere.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Although it may not be expected that differences in the mucosal microbiota would influence plasma cell frequencies in the BM, it has long been appreciated that a large fraction of BM PCs in people secrete IgA, and in unpublished data we have noted that overall frequencies of total immature and mature BM plasma cells can vary greatly depending on the animal colony in which the mice in question are housed. Therefore, one potential explanation for the observed discrepancies between Chu et al versus the data reported here and by Haberland et al [20], is that the modest impact of eosinophil loss on BM PC pools can be realized only in the context of additional signals generated by unique collections of microbes. In this regard, it will be important to distinguish the impact of the microbiota on immature versus mature PC pools in the BM and elsewhere.…”
Section: Discussioncontrasting
confidence: 78%
“…versus the data reported here and by Haberland et al. , is that the modest impact of eosinophil loss on BM PC pools can be realized only in the context of additional signals generated by unique collections of microbes. In this regard, it will be important to distinguish the impact of the microbiota on immature versus mature PC pools in the BM and elsewhere.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The essence of humoral immunity is a stable antibody titer over decades provided by memory plasma cells (mPC). However, there seems to be a high degree of redundancy among the producers of these survival factors (11,12), and also other dynamic accessory cells, such as megakaryocytes (13), basophils (14), or dendritic cells (DCs) (15) are able to promote the survival of mPCs. MPCs reside in a specialized microenvironment in the bone marrow (BM)-the so-called survival niche.…”
mentioning
confidence: 99%